THE DEVELOPMENT OF EDUCATION IN UKRAINE AT THE BEGINNING OF THE XXIST CENTURY: CHANCES AND CHALLENGES - Mukan, Nataliya; Blavt, Oksana (Mountain School of Ukrainian Carpaty, 2019)
In the article the main trends of education development in Ukraine at the beginning of the XXIst century have been studied. In accordance with education reformation as well as its modernization processes in all spheres the main attention has been paid to its innovative development. The importance of the study is due to the objective need to improve the effectiveness of education at all levels in line with contemporary social development in order to successfully integrate into the European space. The purpose of the study is to identify the main directions of the development of education in the context of modernization at the beginning of the XXIst century. The research is based on the use of a set of general scientific theoretical methods: analysis and synthesis, abstraction, formalization. The scientific research has substantiated that the positions and directions of exploration of educational development pathways should be directed firstly to a radical restructuring of the educational sector, and secondly to the modernization of this process through the use of innovation. An overview and analysis of the priority directions of education modernization are presented. The implementation of them provides development at all its levels, increasing the efficiency of the educational process and obtaining qualitatively new results. The following direction are distinguished: the implementation of interdisciplinary and project approaches, globalization and internationalization of education, intensive development and widespread use of information and communication technologies, taking into account andragogical principles of training, professional mobility of a specialist in the vertical and horizontal dimensions, the insurance of possibilities for lifelong education. It has been found that a significant direction of education development, foreseen by the new educational paradigm, is the application of the type of sociocultural inheritance from the future to the modern, that means the realization of the concept of “lifelong learning”, which is transformed into the idea of continuous education. It is determined that one of the priority directions of educational branch modernization is the objective necessity of innovations integration into the process of teaching staff professional training. According to the results of scientific research, it is defined that the integration of modernization processes in education causes the emergence of application of new approaches to the educational process organization of an advanced nature, which outline the future direction of the system development. The results of the study complement the information on the need for active implementation of modernization technologies in the educational process, relevant to modern social development, which is now the most important strategic priority for the sustainable development of education. The implementation of identified trends in education development in the context of modernization is aimed at radical changes that will allow to change and develop the educational process in order to achieve higher results and to formulate a qualitatively different educational practice.